A High-Conversion Ratio Multiphase Converter Realized with Generic Modular Cells - Eli Hamo; Michael Evzelman; Mor Mordechai Peretz (Applied Sciences, 2025)
This paper introduces a high-conversion ratio multiphase nonisolated converter built from generic LC cells. The unique architecture that hinges on a generic capacitor inductor switching module enables the high modularity of the topology, providing a quick extension of the converter design in an interleaved configuration for lower ripple and higher current output. The generic module comprises the basic power components of a nonisolated DC–DC converter, where the unique interaction between the capacitor and the inductor results in a soft charging operation, which curbs the losses of the converter, and contributes to a higher efficiency. Additional features of the new converter include a significantly extended effective duty ratio, and a lower voltage stress on the switches, a very high output current, and architecture-inherent output current sharing that balances the loading between the phases. In addition, a power extension using a paralleling and interleaving approach is presented to provide higher output current capabilities. Simulation and experimental results of a modular interleaved three-phase prototype demonstrate an excellent proof of concept and agree well with the theoretical analyzes developed in this study.